#TITLE_ALTERNATIVE# - ASRIELSYA BUYA BAMARIESHA (NIM : 15110007) ; Pembimbing I : Dr. techn. Dudy D. Wijaya, ST., M.Sc
The GNSS (Global Navigation Satellite System) signals propagate through the whole ionosphere, hence the GNSS signals bring a complete information on the ionosperic parameters. However, ionospheric sensing using a single GNSS receiver can only be used to determine one ionospheric parameter, i.e. Total Electron Content (TEC). In this research, a new method for determination of ionospheric parameters using a single GNSS receiver was proposed. This new method is based on the improved formula for the Geometry Free linier combination that is able to directly estimate the ionospheric TEC and slab thickness. These parameters can then be used to determine the critical frequency of the F2-layer (foF2), which is usually determined using ionosonda technique. FoF2 is defined as the highest frequency signal that will reflect back from F2 layer to its transmision location. With GNSS network in Indonesia, this new method has potential to study spatial and temporal characteristic foF2 parameter in high resolution. The results from the GNSS observation at Badan Informasi Geospasial (BIG) during 2011-2012 were validated by those from ionosonda technique. The correlation coefficient and RMS error between those techniques are about 0.91-0.95 and 0,2-1,2 MHz. The validation results show that the GNSS technique produces a good agreement result with those of the ionosonde technique.